Partisipasi Masyarakat dalam Meningkatkan Ekowisata Mangrove di Desa Denai Kuala, Kabupaten Deli Serdang - Meilinda Suriani Harefa; Restu Restu; Theresia Margaretha Gulo; Irfan Ruhaimi; Jenni Novita Sianturi (Lembaga Pengembangan Kinerja Dosen, 2024)
Mangrove ecotourism offers various interesting tourist activities for visitors, such as nature tourism, environmental education and cultural tourism. The aim of this research is to determine the role and efforts of the community in participating in improving mangrove ecotourism management in Denai Kuala Village, Pantai Labu District, Deli Serdang Regency. The method used in this research is qualitative with a descriptive approach. The results of this research show that Monkey Beach is managed with an approach that harmonizes environmental protection, animal welfare, education and economic sustainability. The management of mangrove ecotourism on Putra Deli beach is managed by one party where the management of the beach income is used properly and part of it goes into the treasury as funds for further beach management. Muara Indah Beach Mangrove management is carried out by community groups who live around the beach. Not all people, only a few are included in the Muara Indah Beach management group.